The Role of Human Resource Management in Improving the Sus-tainability and Economic Contribution of BUMDes: A Case Study of Cibodas Village in the Post-Pandemic Era - Monika Balqis Pratiwi; Ahmad Badawi Saluy; Didin Hikmah Perkasa (Pusat Riset dan Inovasi Nasional, 2025)
Village Owned Enterprises (BUMDes) is a type of legal entity business that can be used as a form of effort to improve the village economy and increase Village Original Income (PADes). One of the villages that founded BUMDes is BUMDes Karya Mandiri in Cibodas Village, Lembang District, West Bandung Regency. This research aims to analyze how the role of Village-Owned Enterprises (BUMDes) in helping to increase Village Original Income (PADes) in Cibodas Village, Lembang District, West Bandung Regency. Research methods use qualitative with a descriptive approach. Data collection techniques include interviews, observations, and documentation. The results of the research show that the management of BUMDes Karya Mandiri is quite good and meets the 6 principles of BUMDes management. BUMDes Karya Mandiri has been able to increase the Village’s Original Income as evidenced in 2019, 2021, and 2022 BUMDes gave 42,000,000 IDR to PADes and in 2023 BUMDes gave IDR 15,300,000. Although the number of contributions is still relatively small compared to the income obtained by BUMDes, but with the existence of BUMDes it is able to increase PADes and help improve the community’s economy. BUMDes in improving PADes there are supporting and Inhibiting factors. The supporting factors of BUMDes are Central Government Support, Village Government Support, Potential Resources owned by the Village, Knowledge of Human Resources, and Business Capital or Budget. Meanwhile, the factors that hinder the role of BUMDes in increasing the Village’s Original Income are Financial Management, Human Resources (Society), Natural Factors, and Unutilized Potential.